Sociological study regarding Romanian manager’s motivation - SCÂRNECI, Florentina (Annals of Spiru Haret University. Economic Series, 2010)
The article presents the results of a qualitative research (conducted in 2008) on the Romanian manager’s identity (insisting only on the motivational aspects). 45 managers were interviewed and the data obtained were analysed and interpreted qualitatively (using grounded theory procedures). The motivational factors identified were then tested by means of a pilot study (a questionnaire applied on 207 subjects). The methodological aspects of the researches (concerning data collection, analysis, and interpretation) are detailed in the article. Here are some hypotheses resulted from the pilot study: managers unlike non-managers are motivated by difficult tasks, with great responsibilities and by the need for increased power; the performed managers unlike those that are not so performing are motivated by an even more increased need for power and by the strong wish to be promoted.